PENINGKATAN KESADARAN DAN PENGETAHUAN MASYARAKAT TENTANG HAK-HAK HUKUM DAN PERLINDUNGAN KORBAN PERDAGANGAN ORANG MELALUI PROGRAM EDUKASI DAN PENYULUHAN - Pupu Sriwulan Sumaya (ADIMA Jurnal Awatara Pengabdian Kepada Masyarakat, 2024)
The community service program in Cirebon aims to increase legal awareness of the community regarding their rights and protection of victims of human trafficking. Through the implementation of counseling involving interactive methods such as group discussions, case simulations, and question and answer sessions, the program successfully increased participants' understanding of the signs of human trafficking, legal rights, and reporting mechanisms. Evaluation results showed that around 75% of participants reported increased knowledge and readiness to report human trafficking cases. However, challenges such as lack of community confidence in reporting cases and uncertainty about the legal process still exist. The program also identified the importance of local community involvement and adapting educational materials to the local context for greater effectiveness. The evaluation showed that ongoing follow-up is needed to maintain community understanding and improve the effectiveness of human trafficking prevention. These findings provide a basis for the development of a more comprehensive and sustainable education strategy in the future, with the hope of strengthening victim protection and human trafficking prevention at the local level.